WINTER WHEAT YIELD CAPACITY IN SHORT-ROTATION ROW CROP SUCCESSION DEPENDING ON FERTILIZATION AND BASIC SOIL TILLAGE - Filonenko, S. V.; Tyshchenko, M. V. (Scientific Progress & Innovations, 2020)
Using optimal fertilization system and conducting rational basic soil tillage under all rotation crops favor winter wheat yield increase. However, there are not enough experimental data concerning the effect of fertilization and practices of soil cultivation on winter wheat grain productivity in the zone of insufficient moistening. So, these are the topicality and practical importance of the present studies, the aim of which is establishing the impact of basic soil cultivation systems on winter wheat yields under organic and mineral fertilization systems in short-rotation row crop succession. The task of the research was to identify the influence of different techniques of basic soil tillage on grain productivity of winter wheat; study the effect of various fertilization systems used during cultivating crops in short-rotation row crop succession, the output of winter wheat grain; investigate and analyze winter wheat grain productivity under complex effect of proceeding crops on it, and also fertilization and soil tillage methods. Corresponding field experiments were conducted in the Left-Bank Forest-Steppe of Ukraine, in particular, during permanent experiment at Veselyi Podil Experimental Selection Station (in Semenivka district, Poltava region) of the Institute of Bio-Energy Crops and Sugar Beet of the National Academy of Agrarian Sciences of Ukraine during 2015-2018. As a result of the studies, it has been established that in short-rotation row crop succession, 20-22 cm deep plowing under silage corn, 30-32 cm deep plowing under sugar beet, and 10-12 cm shallow soil tillage under winter wheat and spring barley applying 6.25 t of manure + N33.8Р33.8К33.8 without straw and sugar beet tops per 1 ha of plow land during crop rotation resulted in the highest winter wheat grain yield – 4.61 t/ha. Plowing under all crops against a background without fertilizers, straw, sugar beet tops, and also plowing combined with applying 6.25 t of manure + N33.8Р33.8К33.8 + straw + sugar beet tops per 1 ha of plow land during crop rotation ensured significant winter wheat yield increase in comparison with the variants, in which soil was plowed exclusively under row crops and shallow soil tillage was conducted under cereals (using corresponding identical fertilization systems of the variants).